WHAT’S BEHIND BRAND SWITCHING AMONG INDONESIAN CUSTOMERS: IS IT ALL ABOUT BRAND IMAGE AND CUSTOMER SATISFACTION? - Munawaroh, Nuril Aulia; Sudarmiatin, Sudarmiatin (Transpublika Publisher, 2024)
The study focuses on individuals who consume fast-moving consumer goods and uses a cross-sectional time frame. The data was collected using Google Forms and a snowball sampling method, with a total of 300 samples gathered. The study found that product quality, customer satisfaction, and brand image are significant factors in brand-switching behavior. The study also found that product quality has a significant relationship with all variables, including brand switching, customer satisfaction, and brand image. The study used partial least squares structural equation modeling (PLS-SEM) to analyze the data and found that product quality is positively and significantly related to brand switching through customer satisfaction and brand image. The study concluded that product quality plays a crucial role in brand-switching behavior and customer satisfaction. The research suggests that companies should focus on building and maintaining a favorable brand image to retain customers and prevent brand-switching. By understanding the relationship between product quality, customer satisfaction, and brand image, businesses can develop effective strategies to enhance brand loyalty and drive long-term success in the competitive FMCG market.